eProject User Experience: The Reality - Sandler, John (International Journal of Advanced Corporate Learning (iJAC), 2010)
Corporate eProjects have become fast-paced and increasingly demanding. More often than not, problems and challenges readily surface within technology projects. These can often stem from poor usability and user experience aspects of the development process, together with lack of adequate communications plans and strategies.Successful forward planning and succinct on-going communication of development and testing processes is critical.Clear communications across the range of impacted user work groups, together with the project team, ensuring an understanding of all roles in the development process is vital. Understanding the need to engage expert users and representatives from the impacted user groups is also critical.This paper and associated presentation will look at what can happen in the real world, when even highly detailed project planning can be undermined by a lack of communications, understanding and unsatisfactory project team user experience. In effect, the user experience of project teams.